Rebranding Mergers: How attitudes influence consumer choices? - César - Machado, Joana (2012)
In the context of a merger or an acquisition, the management of corporate identity – in particular of corporate brand names and logos – assumes a critical role. The purpose of this article is to provide a better understanding of the corporate brand redeployment decision, considering the reactions of one important stakeholder group – consumers. This study develops a typology of the various corporate identity structures that could be assumed in the context of a brand merger, and analyses how consumers' attitudes towards the corporate brands influences their preferences regarding the different branding strategies. Results suggest that the preference for a monolithic redeployment strategy, suggested in previous studies, is only clearly supported when one of the partners in the merger is a weak partner. When the merger involves two familiar brands, there is a tendency among consumers to combine elements of both brands' identity. Finally, it is concluded that the affective and behavioural dimension of attitude towards the brand has a significant influence on consumers' preferences.